Rekonfigurasi Jaringan 20 kV Feeder Balam Dengan Metoda Binary Particle Swarm Optimization (BPSO) Di PT. PLN (Persero) Bagan Batu - Simanjuntak, Roberto; Tanjung, Abrar; Zulfahri, Zulfahri; Putra Halilintar, Masnur (Teknik Elektro Universitas Lancang Kuning, 2021)
Distribution of electrical energy by PT. PLN (Persero) Bagan Batu Rayon is supplied by a 20 kV feeder Balam distribution channel through Bagan Batu Substation. The total length of the Balam feeder network is 85,550 kms, the Balam feeder load to meet electrical energy needs is quite high. So that it causes power losses and voltage drop is quite high. To reduce the occurrence of voltage drop and on bus 10, 11,12,13,14 and 15 with the lowest voltage at the end of the channel reaches 16,7 kV. Analysis with Newton Rapshon method using MATLAB (R2007b) software is used to determine the results of voltage and power loss to be minimized. Based on the results of the discussion on the condition of the lowest voltage of 16.7 kV with an active power of 0.045 MW and reactive 0.121 MVAr on the bus 10.11,12,13,14 and 15. After reconfiguration using Newton Rhapson method with MATLAB (R2007b) software, obtained the lowest voltage of 19.2 kV with an active power of 0.039 MW and reactive power of 0.101 MVAr on the second reconfiguration. The results of the research show that by designing two new channels with the Binary Particle Swarm Optimization (BPSO) method can find a new configuration that minimizes losses. Active power losses resulting from the new reconfiguration are 0.027 MW and reactive power is 0.092 MVAr.